Generation Z's Perceptions of the Practicality and Convenience of Online Shopping - Budiana Budiana; Fitri Faujiah; Aldiansyah Aldiansyah (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
This study aims to analyze Generation Z's perceptions of the practicality and convenience of online shopping through various e-commerce platforms such as Shopee and TikTok Shop. Generation Z is known as a generation of digital natives who are familiar with technology and have a high tendency to shop online because it is considered faster, easier, and more efficient than conventional shopping. The research method used was descriptive qualitative with five respondents selected by purposive sampling. Data were collected through an open questionnaire containing ten questions about experiences, views, and motivations for online shopping. The results showed that practicality, time efficiency, and promotions were the dominant factors that increased the convenience of shopping. The respondents considered that online shopping facilitated their daily activities because it could be done anytime without having to leave the house. Trust factors, such as transaction security and product review reliability, also played an important role in shaping positive perceptions of online shopping. In addition, the availability of promotions, discounts, and free shipping had a significant influence on purchasing decisions. This study concludes that the combination of ease of access, economic value, and security are the main factors that shape Generation Z's perception of the convenience and practicality of online shopping in the digital age.